SENGKETA TANAH DALAM PENJUALAN TANAH KAS DESA: (STUDI KASUS DESA NGRIMBI KECAMATAN BARENG KABUPATEN JOMBANG TAHUN 2010–2014) - Sucipto Sucipto; Rini Winarsih (Fakultas Hukum Universitas Darul Ulum, 2022)
The purpose of this study was to describe and analyze the stages of land disputes that occurred in Ngrimbi Village due to land sales carried out by the Ngrimbi Village Head for the period 2008-2012 using Simoe Fisher's conflict theory. This research is a qualitative research with the type of case study research. Data collection techniques in this study used interview and observation techniques. The results of this study indicate that conflict occurs in five stages: pre-conflict, confrontation, crisis, consequence, and post-conflict. The pre-conflict was marked by the formation of an agency to restore village assets by the village head and deliberately appointing his family as chairman. This action was carried out without coordination with the BPD and without the knowledge of the community. The village assets returned were village land, but the land was sold so that the people who knew did not accept it. The conflict continued to the confrontation stage with demonstrations and minor clashes between the community and supporters of the village head. In the next stage, a crisis occurs as the peak of the conflict is marked by mutual reports between the two parties. As a result, the village head and his family who were appointed to lead the village asset recovery agency were punished and received persecution from the community. The post-conflict itself was seen after several years had passed with the election of a new village head who tried to end all disputes by holding deliberations so that the community would know that the village assets in the form of land had been returned to the village.